2009
DOI: 10.1002/cncr.24460
|View full text |Cite
|
Sign up to set email alerts
|

Vinflunine in platinum‐pretreated patients with locally advanced or metastatic urothelial carcinoma

Abstract: BACKGROUND: The activity and safety of vinflunine was evaluated in patients with locally advanced or metastatic urothelial carcinoma (UC) who developed disease progression within 12 months of platinum‐containing chemotherapy. METHODS: Patients with UC were eligible if they received a prior platinum‐based regimen in the neoadjuvant/adjuvant setting or as first‐line treatment for advanced/metastatic disease and had developed disease progression within 12 months. Vinflunine was administered intravenously every 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 15 publications
3
67
1
3
Order By: Relevance
“…Toxicity consisted mainly of grade 3 or 4 neutropenia (67%) and febrile neutropenia (5%) 60 . The second trial included 175 patients with platinum-refractory bc, and in 150 patients, the or rate was 15%, with a mds of 8.2 months and a more favourable toxicity profile 65 . Based on those results, a large phase iii trial randomized 370 patients to receive either vfl with bsc or bsc alone 64 .…”
Section: Single-agent Second-line Therapymentioning
confidence: 99%
“…Toxicity consisted mainly of grade 3 or 4 neutropenia (67%) and febrile neutropenia (5%) 60 . The second trial included 175 patients with platinum-refractory bc, and in 150 patients, the or rate was 15%, with a mds of 8.2 months and a more favourable toxicity profile 65 . Based on those results, a large phase iii trial randomized 370 patients to receive either vfl with bsc or bsc alone 64 .…”
Section: Single-agent Second-line Therapymentioning
confidence: 99%
“…Compared to other vinca alkaloids, VFL has shown a better safety profile, inducing a smaller degree of neuropathy and its early resolution after drug withdrawal. [13][14][15][16][17][18] Other adverse events reported were mucositis and neutropenia, which were of low grade and of prompt resolution after the appropriate therapy. In the phase III trial conducted by Bellmunt et al, 16 VFL has demonstrated the ability to improve the outcome of patients with advanced UC which progressed after a first-line cisplatin-containing chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, VFL did not induced the dose-limiting neurotoxicity observed for other vinca alkaloids. [13][14][15][16][17] More recently, Harshman et al 17 studied the possible impact of a prior first-line cisplatin chemotherapy on the outcome of patients enrolled in the aforementioned trial. 16 As expected, the impact of VFL on the outcome was independent of prior chemotherapy; the drug was able to prolong OS among in both cisplatin-pretreated patients and those who did not receive cisplatin.…”
Section: Phase III Trialsmentioning
confidence: 99%
See 2 more Smart Citations